Phase I trial of cetuximab in combination with capecitabine, weekly irinotecan, and radiotherapy as neoadjuvant therapy for rectal cancer - Hofheinz, Ralf-Dieter; Horisberger, Karoline; Woernle, Christoph; Wenz, Frederik; Kraus-Tiefenbacher, Uta; Kähler, Georg; Dinter, Dietmar; Grobholz, Rainer; Heeger, Steffen; Post, Stefan; Hochhaus, Andreas; Willeke, Frank (International journal of radiation oncology, biology, physics, 2006)
Purpose: To establish the feasibility and efficacy of chemotherapy with capecitabine, weekly irinotecan, cetuximab, and pelvic radiotherapy for patients with locally advanced rectal cancer. Methods and materials: Twenty patients with rectal cancer (clinical Stage uT3-T4 or N+) received a standard dosing regimen of cetuximab (400 mg/m(2) on Day 1 and 250 mg/m(2) on Days 8, 15, 22, and 29) and escalating doses of irinotecan and capecitabine according to phase I methods: dose level I, irinotecan 40 mg/m(2) on Days 1, 8, 15, 22, and 29 and capecitabine 800 mg/m(2) on Days 1-38; dose level II, irinotecan 40 mg/m(2) and capecitabine 1000 mg/m(2); and dose level III, irinotecan 50 mg/m(2) and capecitabine 1000 mg/m(2). Radiotherapy was given to a dose of 50.4 Gy (45 Gy plus 5.4 Gy). Resection was scheduled 4-5 weeks after termination of chemoradiotherapy. Results: On dose level I, no dose-limiting toxicities occurred; however, Grade 3 diarrhea affected 1 of 6 patients on dose level II. Of 5 patients treated at dose level III, 2 exhibited dose-limiting toxicity (diarrhea in 2 and nausea/vomiting in 1). Therefore, dose level II was determined as the recommended dose for future studies. A total of 10 patients were treated on dose level II and received a mean relative dose intensity of 100% of cetuximab, 94% of irinotecan, and 95% of capecitabine. All patients underwent surgery. Five patients had a pathologically complete remission and six had microfoci of residual tumor only. Conclusion: Preoperative chemoradiotherapy with cetuximab, capecitabine, and weekly irinotecan is feasible and well tolerated. The preliminary efficacy is very promising. Larger phase II trials are ongoing. (c) 2006 Elsevier Inc.